Genetic diversity of yield related traits in a large subset of exotic and indigenous rice germplasm collection maintained at Tamil Nadu Agricultural University gene bank - Amudha, K; Ariharasutharsan, G (ORYZA-An International Journal of Rice, 2021)
The present investigation was carried out to explore the extent of genetic divergence in 95 rice germplasm accessions for twelve characters during kharif, 2018. In D2 analysis, the 95 genotypes were grouped into fifteen clusters. The clustering pattern indicated that there was no parallelism between genetic diversity and geographical origin as the genotypes from same origin were included in different clusters and vice versa. The highest intra cluster distance was registered in cluster V (215.183) followed by cluster IX (209.831), cluster VIII (204.057) and cluster XIV (202.623).The maximum inter cluster distance was observed between cluster II and cluster III (991.049) followed by cluster II and cluster X (974.960), cluster III and cluster XI (963.826), cluster II and XII (962.013), cluster X and cluster XI (932.469) and cluster XI and cluster XII (919.151). Genetically distant parents from those clusters could be able to produce higher heterosis in progenies on hybridization. Grain yield per plant, 100 grain weight and days to 50% flowering were the major contributors towards the total genetic divergence among the genotypes studied. Thus selection could be made based on grain yield per plant, hundred grain weight and days to 50%flowering for the progenies identified.